1998
DOI: 10.1038/sj.bjp.0701968
|View full text |Cite
|
Sign up to set email alerts
|

Increase in tumor necrosis factor‐α production linked to the toxicity of indomethacin for the rat small intestine

Abstract: 1 The toxic e ects of nonsteroidal anti-in¯ammatory drugs for the lower gastrointestinal tract share certain features with in¯ammatory processes, suggesting that the release of in¯ammation cytokines such as TNF-a may damage the intestine. 2 Rats received a s.c. injection of indomethacin. Then, jejunum-ileum was taken up for the quanti®cation of ulcerations, production of TNF-a, nitrites and PGE2 ex vivo and activity of calciumindependent NO synthase and myeloperoxydase. Activation of NO metabolism and myeloper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 39 publications
(58 reference statements)
7
77
0
Order By: Relevance
“…In contrast, it has been reported that persistent and marked blockage of TNF-α bioactivity may have a detrimental effect on acute intestinal inflammation in a dextran sulfate sodium (DSS)-induced colitis model in mice (10). On the other hand, TNF-α is increased in indomethacin-induced intestinal ulcerations in rats and is involved at an early stage of NSAID toxicity in the small intestine (11). TNF-α may up-regulate other cytokines and pro-inflammatory mediators, and thereby cause tissue damage through the gradual rise in serum IL-1β and inducible nitric oxide synthase (iNOS)-derived NO levels (12).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…In contrast, it has been reported that persistent and marked blockage of TNF-α bioactivity may have a detrimental effect on acute intestinal inflammation in a dextran sulfate sodium (DSS)-induced colitis model in mice (10). On the other hand, TNF-α is increased in indomethacin-induced intestinal ulcerations in rats and is involved at an early stage of NSAID toxicity in the small intestine (11). TNF-α may up-regulate other cytokines and pro-inflammatory mediators, and thereby cause tissue damage through the gradual rise in serum IL-1β and inducible nitric oxide synthase (iNOS)-derived NO levels (12).…”
Section: Introductionmentioning
confidence: 78%
“…Several lines of evidence support this hypothesis: (i) neutrophil depletion by intraperitoneal injection of anti-neutrophil antibody significantly attenuates the intestinal mucosal injury induced by indomethacin (13,16); (ii) intravital microscopic evaluation of the mesenteric circulation has shown that indomethacin promotes neutrophil adherence and emigration in post-capillary venules (23); and (iii) the induction of intestinal TNF-α production by NSAIDs was followed by activation of the neutrophil activation pathway (MPO activity) in the inflammation cascade, which could contribute to jejunum-ileum lesions (11). In this study, we have shown that MPO activity, an index of tissue-associated neutrophil accumulation, and the expression of KC mRNA, which is involved in chemotaxis and cell activation of neutrophils, were remarkably enhanced in the indomethacin-treated intestinal mucosa, and that these increases were significantly reduced in TNF-α -/-mice compared with WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, TBARS and MPO activity in the small intestine were significantly increased after indomethacin treatment, and these responses were significantly inhibited by tacrolimus at the dose that prevented the development of intestinal lesions. On the other hand, Bertrand et al (27) demonstrated the involvement of TNF-α in the pathogenic mechanism of these lesions, especially in the early event preceding the elevation of NO production and MPO activity as well as lesion formation. TNF-α is known to induce the expression of iNOS in various cells including leukocytes (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The ceca from rofecoxib-and aspirin-treated animals were normal in appearance. Gross intestinal injury of indomethacin-treated rats has been well documented (Yamada et al, 1993;Bertrand et al, 1998), but not as thoroughly for ibuprofen. Histologically, either multifocal epithelial ulceration or inflammatory cell infiltrates were observed within the small intestine of ibuprofen-and indomethacintreated rats.…”
Section: Drug Signatures For the Acute Phase Responsementioning
confidence: 99%